Compared investigation of carbon-decorated Na3V2(PO4)3 with saccharides of different molecular weights as cathode of sodium ion batteries. (1st October 2018) - Liu, Xiaohong; Wang, Enhui; Feng, Guilin; Wu, Zhenguo; Xiang, Wei; Guo, Xiaodong; Li, Juntao; Zhong, Benhe; Zheng, Zhuo
Abstract: A critical issue to boost the development of sodium ion batteries is the development of advanced active materials via meticulous understanding of the synthesis process. The practical application of sodium vanadium phosphate (Na3 V2 (PO4 )3 ), which shows high energy density, stable structure and excellent thermal properties, is hindered by the intrinsic poor electronic conductivity. Carbon coating was proved to be an effective strategy to cover such pristine limitation and deserved systematic and intensive investigation. Herein, saccharides that widely distributed in nature with different molecular weights were selected to identify the function mechanism of carbon sources in preparing Na3 V2 (PO4 )3 @C composite via solid state reaction. Comprehensive and systematic results evidenced that the high polymer starch with glucose polymerization could construct three-dimensional interconnected carbon network, which would boost the electron conductivity and stabilize the structure upon repeated sodium ions insertion/extraction. As a consequence, the extraordinary high rate capability and long-time stability were obtained: a high rate capacity of 72 mA h g −1 could be delivered even at 40 C and the cell retained a capacity retention of 82.8% after 1000 cycles at 1 C. We believe that our work presents here would provide important insights into the carbon coating strategy, which will be favourable for accelerating the commercialization of SIBs.